cGAS-STING Signaling Pathway and Liver Disease: From Basic Research to Clinical Practice - Chen, Bangjie; Rao, Xianyue; Wang, Xinyi; Luo, Zhipan; Wang, Jianpeng; Sheng, Shuyan; Liu, Yuchen; Zhang, Ning; Jin, Shiyu; Chen, Haosong; Sun, Chenyu; Xu, Tao; et al. (Frontiers in Pharmacology, 2021)
cGAS-STING signaling pathway is an autoimmune inflammatory pathway discovered in 2013, which can trigger the expression of a series of inflammatory factors represented by type 1 interferon. As an important immune organ, cGAS-STING signaling pathway plays a significant role in liver physiology. Recent studies have found that cGAS-STING signaling pathway is closely related to the progress of liver diseases. For example, activation of cGAS-STING signaling pathway can significantly inhibit HBV replication in vivo. This review summarizes the role of cGAS-STING signaling pathway in several common liver diseases, especially reviews the current application advances of cGAS-STING signaling pathway in the liver disease therapy, and prospects its future research and application combined with frontier fields, suggesting a potential therapeutic target for liver disease.